2020
DOI: 10.1109/tnse.2019.2896232
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Characterization of Market Power in Electric Power Networks

Abstract: We consider a market in which capacity-constrained generators compete in scalar-parameterized supply functions to serve an inelastic demand spread throughout a transmission constrained power network. The market clears according to a locational marginal pricing mechanism, in which the independent system operator (ISO) determines the generators' production quantities to minimize the revealed cost of meeting demand, while ensuring that network transmission and generator capacity constraints are met. Under the sty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Such sharp price spikes during some periods can be regarded as the result of market power. In addition, the excess monetary loss caused by the aforementioned crisis reached $40 billion and led to the bankruptcy of Pacific Gas and Electric [28], [29], which is also the result of market failure caused by market power.…”
Section: B Empirical Evidencementioning
confidence: 99%
“…Such sharp price spikes during some periods can be regarded as the result of market power. In addition, the excess monetary loss caused by the aforementioned crisis reached $40 billion and led to the bankruptcy of Pacific Gas and Electric [28], [29], which is also the result of market failure caused by market power.…”
Section: B Empirical Evidencementioning
confidence: 99%
“…Moreover, the work of Johari et al (2004) and Johari and Tsitsiklis (2011) showed that such supply offers possess a number of attractive properties including bounded Price of Anarchy and price markups at the Nash equilibrium. The family of supply functions considered here is a capacitated version of those introduced by Johari and Tsitsiklis (2011) that have been studied by Xu et al (2016) and Lin and Bitar (2017) under perfectly inelastic demand. Such supply functions prohibit situations where firms can offer in the market beyond their means.…”
Section: Introductionmentioning
confidence: 99%
“…Em mercados reais de energia, o espaço de estratégias dos geradores não são funções duas vezes diferenciáveis, mas funções definidas pelas regras do leilão. Usualmente, são funções de custo lineares por partes 7 , não decrescentes, com um número máximo de segmentos pré-estabelecido [23,24]. A falta de diferenciabilidade e convexidade estrita deste tipo de função dificulta seu tratamento, motivo pelo qual é comum a literatura recorrer a outros tipos de função.…”
Section: Um Pouco De Contextounclassified
“…A falta de diferenciabilidade e convexidade estrita deste tipo de função dificulta seu tratamento, motivo pelo qual é comum a literatura recorrer a outros tipos de função. Em [24], por exemplo, considera-se como espaço de estratégias funções de custo para um agente j do tipo θ j ln G j G j −g , em que os agentes escolhem o valor de θ j em suas declarações ao operador. A escolha da função se deve ao fato de que, conforme g tende a G j , a função de custo se aproxima assintoticamente a um segmento vertical, representando o fato de que a capacidade é finita.…”
Section: Um Pouco De Contextounclassified
See 1 more Smart Citation